2010
DOI: 10.1108/14637151011049430
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between firm resources and product innovation performance

Abstract: The c~in-en1 issue and full text archive cd tliis joi~rnal is avnilal~le at ww~~.en~eralclinsigh(.co~nll 4(i:I-7154.1111n BPA/JJ 16,3 Assessing the relationship between firm resources and product innovation perf onnance A resource-based viewLily Julienti Ahu Baltar and Hartini A h i n a d

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(68 citation statements)
references
References 51 publications
0
49
2
1
Order By: Relevance
“…For example, Beaver [25] proposed that innovation is vital to the economic development and industrial competitiveness of a country. Bakar and Ahmad [26] also state that the ability to innovate is critical to a company that wants to gain a competitive advantage. A number of studies have also found that technological capability positively affects firm performance [27][28][29].…”
Section: Sustainable Development Of Smesmentioning
confidence: 99%
“…For example, Beaver [25] proposed that innovation is vital to the economic development and industrial competitiveness of a country. Bakar and Ahmad [26] also state that the ability to innovate is critical to a company that wants to gain a competitive advantage. A number of studies have also found that technological capability positively affects firm performance [27][28][29].…”
Section: Sustainable Development Of Smesmentioning
confidence: 99%
“…This approach seeks to maximise the advantages of diversity by training the organisation's members to recognise, acknowledge, and exploit the cultural differences in order to achieve innovation. Culture is actually considered to be one of the most common impediments to the implementation of innovation (Bakar, Julienti, and Ahmad 2010;O'Regan, Ghobadian, and Gallear 2005;Terziovski 2010). The issue of innovation, capabilities, and competitive advantage in Norwegian shipping was considered by Jenssen (2003).…”
Section: Managing Cultural Diversity As a Core Competencymentioning
confidence: 99%
“…Therefore we hypothesized that H2: DC positively influences innovativeness H3: DC positively influences proactiveness H4: DC positive influences risk taking (Rauch et al) and Competitive Advantage (CA) EO is a behavioral model of entrepreneurship in a firm-level that can influences strategic decisions, resource allocations and ability to seize more business opportunities to contributes to competitive advantage (Zahra, Nielsen, & Bogner, 1999), hence it may be considered as intangible valuable assets and capabilities (Covin & Wales, 2011;Rosenbusch, Rauch, & Bausch, 2013). Some researcher considered EO as intangible valuable assets and capabilities, (Bakar & Ahmad, 2010;Covin & Wales, 2011;Rosenbusch et al, 2013), because it influences specific strategic decisions and resource allocations and allow firms to seize more business opportunities. On the other hand, Covin and Miller (2014) conceived EO as an organizational capability, which is a decision-making proclivity favoring entrepreneurial activities.…”
Section: Dynamic Capability (Dc) and Entrepreneurial Orientationmentioning
confidence: 99%